Artificial intelligence in the modern educational space: problems and prospects - Iasechko, S. V.; Ясечко, С. В.; Pereiaslavska, S.; Переяславська, С.; Smahina, O.; Смахіна, О.; Lupei, N.; Лупей, Н.; Mamchur, L.; Мамчур, Л.; Tkachova, O.; Ткачова, О.; et al. (IJCSNS: International Journal of Computer Science and Network Security. - 2022. - Vol. 22, № 6 (June). - P. 25-32, 2022)
Досліджено сучасний стан, перспективи розвитку, розробка та впровадження елементів штучного інтелекту в підготовці майбутнього вчителя. Визначено, що використання елементів штучного інтелекту збільшить ефективність навчального процесу.

The hypothesis of the study of the article is that the use of elements of artificial intelligence will increase the effectiveness of the educational process of the university if: a set of pedagogical conditions for the construction and use of an expert system with elements of artificial intelligence in the educational process of the university is revealed; a model for preparing a future teacher of vocational training for the use of elements of artificial intelligence has been developed; a special course has been developed that contributes to the implementation of the professional orientation of education. In accordance with this, the following tasks were studied in the article: An analysis of scientific and methodological research in the field of the current state, prospects for the development and use of elements of artificial intelligence in the preparation of a future teacher of vocational training and to determine the dynamics of the introduction of intelligent expert systems in education; A set of pedagogical conditions for the construction and use of an expert system with elements of artificial intelligence in the educational process of a university is revealed; It is substantiated to develop a model for preparing a teacher of vocational training to use elements of artificial intelligence.

Исследованы современное состояние, перспективы развития, разработка и внедрение элементов искусственного интеллекта в подготовке будущего учителя. Установлено, что использование элементов искусственного интеллекта увеличит эффективность учебного процесса.
Keywords: Освіта. Педагогіка. Education. Pedagogy. Образование. Педагогика; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; publikatsii u WoS; artificial intelligence; штучний інтелект; искусственный интеллект; innovation; інновації; инновации; intellectual information technologies; інтелектуальні інформаційні технології; интеллектуальные информационные технологии; educational processes; навчальний процес; образовательный процесс